Fahr’s Syndrome; a rare Presentation of Autoimmune Polyendocrine Syndrome-1 and Carbamazepine-Induced Hypothyroidism (Faridpur Medical College Journal, 2025)
Autoimmune polyendocrine syndrome type 1 (APS-1) is an autosomal recessive disorder. Basal ganglia calcification, also known as Fahr’s disease or Fahr’s syndrome, where generalized or partial seizures are one of the common neurological manifestations. However, Fahr's syndrome secondary to APS-1 is extremely rare. This case report describes a 14-year-old girl diagnosed with Fahr’s syndrome linked to APS type 1 in the medicine department of Faridpur Medical College Hospital, Bangladesh. The patient presented with recurrent episodes of generalized seizures over the last 4 years, accompanied by weight loss and progressive darkening of skin. Additionally, she had history of absent adrenarche, thelarche, puberchae and menarchae. She has been taking oral carbamazepine over the last 4 years for seizure. Laboratory investigation reveals adrenal insufficiency, hypoparathyroidism, hypogonadism, and secondary hypothyroidism. A contrast-enhanced MRI of brain shows findings suggestive of Fahr’s disease. She becomes euthyroid after gradual withdrawal of carbamazepine and initiation of sodium valproate.  After administration of glucocorticoid, mineralocorticoid, estradiol, progestin replacement, calcium and Vitamin D supplement her clinical improvement occurred significantly. Eventually her menarchae has started and the patient was referred to Bangladesh Medical University, Dhaka for further management.Faridpur Med. Coll. J. 2025;20(1): 60-63